Pedagogical Reform in Arabic Grammar: Innovating Qawāʿid Instruction through the Card Sort Method - Sofie Maria Ulfa Desvy Kurniasari; Syarifuddin; Miftachul Taubah; Faris Hamid Matar (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study investigates the effectiveness of an active learning model using card sort media to improve students’ understanding of Arabic grammar (qawāʿid) at MTs Darut Taqwa 02. Adopting a quasi-experimental design with a quantitative approach, the study involved 40 ninth-grade students. Data were collected through pretest and posttest instruments. Results showed a notable increase in the average score from 52.75 to 79.25. Observational data also revealed high student engagement across cognitive, affective, and behavioral domains. These findings suggest that the card sort method offers a practical and engaging alternative for grammar instruction, especially in making abstract concepts more concrete and participatory. The study concludes that this approach can foster more meaningful learning and student motivation in Arabic language education.